Cognitive impairment and low health literacy are associated with poor health outcomes in patients with heart failure. (3rd October 2022) - Wu, J; Moser, D
Abstract: Background: Cognitive impairment and low health literacy are prevalent in patients with heart failure (HF). Low health literacy is associated with poor health outcomes, such as frequent re-hospitalizations and increased mortality. Little is known about the relationships among cognitive impairment, health literacy, and health outcomes (HF rehospitalization and cardiac death). Objective: To explore the associations among cognitive impairment, health literacy, and cardiac event-free survival in patients with HF. Methods: This was a longitudinal study of 614 rural patients with HF (male 59%, age 66±13 NYHA class III/IV: 35%). Cognitive function was measured using the Mini-Cog test. Health literacy was measured by the Short Test of Functional Health Literacy in Adults. HF hospitalizations and cardiac mortality were followed at least 2 years and obtained by patient interview, medical record review, and death certificate review. Chi-squares, t-tests, ANOVA, Kaplan-Meier with log rank tests, logistic and Cox regressions were used for data analysis. Results: Two hundred and seven patients (34%) had cognitive impairment. Compared to those without cognitive impairment, patients with cognitive impairment were 2.77 times more likely to have low health literacy (P<0.001). Patients were divided into 4 groups based on cognitive impairment or not and adequate/low health literacy: (1) No cognitive impairment with adequate health literacy; (2) cognitive impairment with adequate health literacy; (3) no cognitive impairment with low health literacy; and (4) cognitive impairment with low health literacy. Both cognitive impairment and health literacy independently predicted cardiac event-free survival. Cardiac event-free survival was worst in those with both cognitive impairment and low health literacy compared to patients in any of the other three groups. Patients with cognitive impairment and low health literacy had 3.5 times higher risk of a cardiac event compared to those without cognitive impairment or low health literacy (P<0.001, Figure). Age, income, angiotensin converting enzyme inhibitor use, beta-blocker use, New York Heart Association functional class, left ventricular ejection fraction, BNP level were significantly different among the four cognitive and literacy groups. Conclusion: Patients with cognitive impairment with low health literacy were at high risk of experiencing a cardiac event. Interventions need to be developed to target high risk patients with cognitive impairment and low health literacy, such as older, low-income patients, to alleviate poor outcomes in patients with HF. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): NIH/NHLBI